QIRA’AH MUBADALAH DAN ARAH KEMAJUAN TAFSIR ADIL GENDER: APLIKASI PRINSIP RESIPROSITAS TERHADAP Q. S. ALI IMRAN: 14 - Anisah Dwi Lastri P (UIN ANTASARI BANJARMASIN, 2020)
AbstractThe issues of discrimination against women are not new in the history of humanity. It is noted that this discrimination has existed since pre-Islamic. Islam, with the rahmatan li al-alamin’s concepg, gaee nee breagh so as go speak gheir preeionslç marginalized righgs ghrongh ghe Holç message. The eomen’s hnmanigarian sgrnggle ghag had been so rigid and focnsed on eomen’s obligagion eighong regard for gheir righgs became more flexible. Bng ghis sgepping-stone that was built by Islam is not necessarily a prerequisite. This is seen in a number of qur 'an verses that seem to place a man as superiority so that often the masculine interpreters appear. This too has a great renown interpretation and has repeated discrimination against women. One of the most sexist texts that is Q. S. Ali Imran: 34 that places women as world jewelry for men without seeing the position of man in women's eyes. The qira 'ah mubadalah notion of giving a fresh breeze to sexist interpretations and making new offers to interpretation styles in particular that are meant to be meant for one subject only. With the mubadalah’s perspecgiee or ghe reciprocigç’s principle, ghe ingerpregagion of Ali Imran: 14 resnlgs in geo cengral ideas, (1) both have the same possibility as being